Pembinaan kepada Kaum Muda Mengenai Jodoh dan Pekerjaan di Jambore Gereja Kristen Kerasulan Indonesia 2022 - Sunarto, Sunarto; Prianto, Robi; Tampubolon, Yohanes Hasiholan; Tiladuru, Vena Melinda; Selan, Yustus; Sihombing, Aeron Frior (Society : Jurnal Pengabdian Masyarakat, 2022)
Youth is a period full of energy and high enthusiasm to gain knowledge and experience in order to achieve what you want. In the midst of globalization and technological advances, it is hoped that young people will not only be able to develop themselves, but also play a role as inheritors and successors of Christian values for a church. Seeing this fact, the implementation of guidance regarding matchmaking and work was carried out by the PkM team of the STT SAPPI Theology Study Program at the 2022 GKKI Youth Jamboree for 1 day and 2 meetings. Based on the results of joint activities with GKKI youth, it was concluded that the participants participated enthusiastically in the activities when they heard and discussed the material presented. This means that the topic of marriage and work is a very relevant topic for the lives of youth and adolescents. In the midst of the rapid development of contemporary values, youths are also expected to have Christian values that can become their guide, especially when considering issues related to their mate and work.